Risk factors for malignant transformation of hepatocellular adenoma to hepatocellular carcinoma: protocol for systematic review and meta-analysis - Johann Pratschke; Tharusan Thevathasan; Teresa Colbatzky; Moritz Schmelzle; Felix Krenzien (BMJ Open)
Introduction Hepatocellular adenomas (HCAs) are solid liver tumours that are usually found incidentally during routine medical check-ups. Multiple modifiable and non-modifiable factors constitute a risk for the malignant transformation of HCAs to hepatocellular carcinoma (HCC), which has emerged to be one of the fastest growing causes of cancer-related mortality globally. This study protocol for a planned systematic review and meta-analysis documents the methodological approach to identify risk factors and their risk estimates for the transformation from HCA to HCC.Methods and analysis Two independent reviewers will systematically search and extract data from studies in patients of all ages published between January 1970 and June 2021 on PubMed, MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, Scopus Web of Science, Ovid, The Cochrane Hepatobiliary Group Controlled Trials Register and The Cochrane Central Register of Controlled Trials by using an a priori defined search strategy. Study quality will be rated with the National Institute of Health quality assessment tools. Disagreements will be resolved by consensus with a third independent reviewer. The primary outcome will be the odds ratio (OR) of developing HCC in patients with prediagnosed HCA depending on the exposure to risk factors. HCC diagnosis must be inferred based on imaging techniques or pathology. We will use R V.4.0.2 to conduct meta-analyses and generate pooled ORs based on random effects models. Results will be presented as forest plots. Cochran’s Q and I2 test will be performed to assess heterogeneity between included studies. Funnel plots and Egger’s weighted regression will be used to evaluate publication bias.Ethics and dissemination No ethical approval is required as we will use and analyse data from previously published studies in which informed consent was obtained. The results will be disseminated in a peer-reviewed journal on completion.PROSPERO registration number CRD42020206578.